2016
DOI: 10.18632/oncotarget.7722
|View full text |Cite
|
Sign up to set email alerts
|

Multi-platform molecular profiling of a large cohort of glioblastomas reveals potential therapeutic strategies

Abstract: Glioblastomas (GBM) are the most aggressive and prevalent form of gliomas with abysmal prognosis and limited treatment options. We analyzed clinically relevant molecular aberrations suggestive of response to therapies in 1035 GBM tumors. Our analysis revealed mutations in 39 genes of 48 tested. IHC revealed expression of PD-L1 in 19% and PD-1 in 46%. MGMT-methylation was seen in 43%, EGFRvIII in 19% and 1p19q co-deletion in 2%. TP53 mutation was associated with concurrent mutations, while IDH1 mutation was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 56 publications
7
20
0
Order By: Relevance
“…Survival data, which were available for 102 patients operated after 2007, after introduction of temozolomide in standard treatment protocols, showed that younger age, IDH1-mutations, MGMT methylation and combined radiation and chemotherapy (temozolomide) were associated with longer survival. This is also in line with previous studies, clearly separating the IDH-wildtype and IDH-mutated subgroups (9,(25)(26)(27).…”
Section: Discussionsupporting
confidence: 93%
“…Survival data, which were available for 102 patients operated after 2007, after introduction of temozolomide in standard treatment protocols, showed that younger age, IDH1-mutations, MGMT methylation and combined radiation and chemotherapy (temozolomide) were associated with longer survival. This is also in line with previous studies, clearly separating the IDH-wildtype and IDH-mutated subgroups (9,(25)(26)(27).…”
Section: Discussionsupporting
confidence: 93%
“…Reference genome used was hg19 from the UCSC Genome Browser database (http://hgdownload.cse.ucsc.edu/goldenPath/hg19/bigZips). Specific regions of 47 genes (panel of pan‐cancer genes of interest related to cancer genomics based on current literature) were amplified using the customized Illumina TruSeq Amplicon Cancer Hotspot panel 11. All variants reported were detected with >99% confidence based on the mutation frequency present.…”
Section: Methodsmentioning
confidence: 99%
“…Specific regions of 47 genes (panel of pan-cancer genes of interest related to cancer genomics based on current literature) were amplified using the customized Illumina TruSeq Amplicon Cancer Hotspot panel. 11 All variants reported were detected with >99% confidence based on the mutation frequency present. Mutations including PTEN, TP53 and BRAF and were evaluated by Nextgeneration sequencing (NGS; Illumina MiSeq platform) (Supporting Information Table S3).…”
Section: Mutational Analysismentioning
confidence: 98%
“…Indeed, several recent studies have provided convincing evidence for molecular drifts occurring during glioblastoma progression after (or under) standard therapy. Xiu et al have compared 12 pairs of patient-matched ndGBs and recGBs and found profound changes in the spectrum of biomarkers including MGMT methylation in 94% of samples analyzed [31]. Importantly, loss of MGMT methylation was found to be a more frequent event than acquisition in recGBs.…”
Section: Glioblastoma: General Factsmentioning
confidence: 99%
“…The past decade has been marked by an explosion of exploratory investigations that have applied high-throughput omics to characterizing (epi)genome, transcriptome and metabolome in ndGBs [42][43][44]. For recGBs, high-throughput profiling data are considerably scarcer [25,[31][32][33]. One of the constraining factors is the limited availability of recGB tissue samples due to the fact that only around 25% of patients are considered for open surgery after recurrence [20] and that diagnostic biopsy is not routinely justified for recGBs due to lack of effective treatment options that can be derived from such a biopsy.…”
Section: Molecular Stratification Of Recurrent Glioblasoma: Challengementioning
confidence: 99%